Numerical calculation of tooth profile of a non-circular curved face gear - Lin, Chao (Strojniški vestnik, 2015)
Based on the cylindrical coordinates and the space engagement theory, which utilize a cylindrical coordinate system, an arbitrary curve equation was obtained and a method of curve expansion was established. This allows any order of pitch curve of non-circular curved face gear and normal equidistant curve parameter equations to be derived. The tooth profile points of the non-circular curved face gear can be solved using the numerical calculation method where the tooth profile intersects with the pitch curve and normal equidistant curves of non-circular curved face gear. Finally the numerical method used to solve the tooth profile of the non-circular curved face gear was proved to be accurate and correct from the small error between measured data and the data of theoretical calculation.
Keywords: analize napak; cilindrične koordinate; numerični izračuni; profil zoba; zobniki z valovito razdelno ploskvijo